Parameter-dependent tribological properties of sinusoidal-textured plasma-sprayed coatings. (October 2022) - Zhan, Xianghua; Liu, Yancong; Yi, Peng; Yin, Xiaoli; Fan, Changfeng; Ma, Jian
Abstract: Texture parameter was an important factor affecting tribological property. In this work, the friction experiments and orthogonal analysis method were combined to investigate the effects of texture parameters on the tribological properties of sinusoidal-textured Ni-based MoS2 coatings under dry conditions. Results showed that only the texture area ratio, width–depth ratio, and angular velocity have significant effects on the tribological properties, and the influence order was as follows: area ratio > angular velocity > width–depth ratio. Good tribological properties could be obtained when the texture area ratio was 9–10%, the angular velocity was 6 rad/s, the width–depth ratio was 0.67–1.36, the amplitude was 0.1 mm, and the relative motion angle was 90°. Highlights: Effects of sinusoidal texture parameters on tribological properties were studied. An orthogonal friction test was designed. Amplitude and relative motion angle have no significant effect on friction. Good tribological properties have optimal texture parameter ranges.